Adaptabilidade e estabilidade de 20 genótipos de soja para a macroregião sojícola 3 - Marchiori, Rodrigo (2008)
This study evaluated the adaptability and stability of 20 soybean genotypes, where 10 of them were lines of the breeding program of Monsoy Ltd. and the other 10 were commercially used controls. The experiments were done in the agricultural years 2005/2006 and 2006/2007, in the soybean macro-region 3 (micro-regions 301, 302 and 303). The experimental design was randomized blocks, with three repetitions. Individual and joint analyses were done, considering genotype yield at the different locations and the averages were compared by the Scott Knott test (1974). Genotype adaptability and stability were evaluated by the methods of Eberhart and Russel, Annicchiarico, Lin and Binns and Centroid. The methods of Annicchiarico, Linn and Binns modified by Carneiro and Centroid presented coherence between them and allowed the identification, among the genotypes evaluated, of those of greater stability and adaptability. The lines 1, 2, 4 and 10 were the ones with general adaptability and stability. Lines 1, 2, and the control 20 were classified as those with adaptability and stability to favorable environments, while lines 3 and 10 and the controls 11 and 14 to unfavorable environments. In the analysis by region, lines 2 and 4 were statistically superior to all others in the regions 301, 302 and 303 and line 10, was simultaneously superior in the regions 301 and 302.